Performance indicators to characterize the water supply to meet the demands of the Lurin River Basin - Olortegui Artica, Christiand (2023)
Water scarcity and the planning of socioeconomic activities are challenges in the management of water resources. Therefore, the objective of this study was to use reliability indicators (RI) to simulate management scenarios in the Lurin River Basin. First, flow rates for the period 1969–2019 were calculated using the EvalHid HBV hydrological model and SIMGES, both from the AQUATOOL decision support system, to simulate demands. The estimation of agricultural demand IRs was made under three conditions: that the deficits for one, two, and 10 years should not exceed 20–40, 40–60, and 80–100% of the annual demand. The goodness-of-fit indices obtained for flow calibration were 0.716, 0.89, and 0.901 for Nash index (NSE), Nash natural logarithm (Ln NSE), and Pearson's correlation coefficient (R), representing the values of satisfactory, very good, and good, respectively. Agricultural demands present annual deficits of 59–96, 92–138, and 333–688% for one, two, and 10 years, so a 50 m3 reservoir is proposed to meet the IR. Thus, the information generated could be used to improve water resource management in the Lurin Basin.